2007
DOI: 10.1017/s0267190508070074
|View full text |Cite
|
Sign up to set email alerts
|

Language and Literacy Development in Computer-Mediated Contexts and Communities

Abstract: This article describes second language uses of Internet communication tools, Web environments, and online gaming, and critically reviews existing research and emerging technologies representing diverse pedagogical conditions in three distinct computer-mediated configurations: (1) instructed and institutional intraclass discussion and interclass partnerships, (2) transcultural partnerships and structured participation in "open" Internet environments, and (3) interaction in ongoing Internet-mediated environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 56 publications
(83 reference statements)
1
62
0
2
Order By: Relevance
“…Social interaction oriented online reading activities (social engagement), such as participating in social networks, E-mailing, or playing collaborative games that involve reading online (e.g. Rama, Black, van Es, & Warschauer, 2012; Thorne & Black, 2007), have been reported to relate negatively to academic achievement and reading skill. Jacobsen and Forste (2011) found that use of social networking sites, use of cell phones for texting, and online gaming had all negative associations with GPA, and both Kirschner and Karpinski (2010), and Junco (2012a) found use of Facebook to be negatively related to students' GPA.…”
Section: Prediction Of Navigation Behaviormentioning
confidence: 99%
“…Social interaction oriented online reading activities (social engagement), such as participating in social networks, E-mailing, or playing collaborative games that involve reading online (e.g. Rama, Black, van Es, & Warschauer, 2012; Thorne & Black, 2007), have been reported to relate negatively to academic achievement and reading skill. Jacobsen and Forste (2011) found that use of social networking sites, use of cell phones for texting, and online gaming had all negative associations with GPA, and both Kirschner and Karpinski (2010), and Junco (2012a) found use of Facebook to be negatively related to students' GPA.…”
Section: Prediction Of Navigation Behaviormentioning
confidence: 99%
“…English language competence in the digital age requires the ability to use the language for internet-mediated communication (Thorne & Black, 2007), which involves new genres, alternative modes of expression, as well as the challenges brought by a more diverse online audience. As a result, the goal of teaching and learning of writing should constitute the development of students' ability to assemble multiple modes in achieving successful communication in response for their target online audience.…”
Section: Technology-enabled Instruction Can Help Students In Their Wrmentioning
confidence: 99%
“…WAEL, exchangeable terms are computer assisted language learning (CALL), blended learning, etc. CALL is rather complicated in that it can be opportunities for language practice, for comprehensible input and interaction, or for the expansion of learners' experience with community where target language is spoken and to connect them with others who engage in such practices as code switching (Thorne & Black, 2007). As Larsen-Freeman and Gameron (2008) stated "Complexity theory aims to account for how the interacting parts of a complex sys-tem give rise to the system's collective behavior and how such a system simultaneously interacts with its environment".…”
Section: Eco-constructivism a Combined Theory Of Constructivism And mentioning
confidence: 99%